Media Representation and Digital Engagement: Analyzing @IndonesianMedicalCenter's Impact on Public Health Communication - Nurul Anisa; Prayudi, Haris; Ramadhani, Alfi (Yayasan Ilomata, 2024)
The development of information technology, especially social media, has changed the landscape of public health communication significantly. One platform that is increasingly popular in disseminating health information is Instagram, with various health accounts that actively present informative content. One prominent account is @IndonesianMedicalCenter (IMC), which has become a trusted source of health information for the Indonesian people. However, there has been no research that specifically examines the impact of these accounts on public health communication. This research aims to analyze the impact of the Instagram account @IndonesianMedicalCenter on public health communication. Through this analysis, it is hoped to better understand how media representation and digital engagement from these accounts influence people's health knowledge, attitudes and behavior The analytical tool used in this research is NVivo. This research uses a qualitative approach with content analysis techniques. Data is collected from posts published by the @IndonesianMedicalCenter account during a certain period. These posts are analyzed to identify the main themes presented, the communication style used, and the interactions between the account and its followers. The analysis results show that the Instagram account @IndonesianMedicalCenter actively disseminates health information that is accurate, relevant and easy to understand. The posts cover a variety of health topics, from disease prevention to promoting healthy lifestyles. Apart from that, this account also plays a role in building an online community that is active in discussing and exchanging information about health. Thus, the @IndonesianMedicalCenter account has a positive impact in increasing health literacy and public health awareness.